Prevalence of and Risk Factors for Anal High-grade Squamous Intraepithelial Lesions in Women Living with Human Immunodeficiency Virus. (11th July 2019) - Stier, Elizabeth A; Lensing, Shelly Y; Darragh, Teresa M; Deshmukh, Ashish A; Einstein, Mark H; Palefsky, Joel M; Jay, Naomi; Berry-Lawhorn, J Michael; Wilkin, Timothy; Wiley, Dorothy J; Barroso, Luis F; Cranston, Ross D; et al.
Abstract: Background: Women living with human immunodeficiency virus (WLHIV) have disproportionately high rates of squamous cell carcinoma of the anus compared with the general population of women. Anal high-grade squamous intraepithelial lesions (HSILs) precede anal cancer, and accurate studies of HSIL prevalence among WLHIV in the United States are lacking. Methods: The AIDS Malignancy Consortium 084 study was a multicenter national trial to evaluate the prevalence of and risk factors for anal HSIL in a US cohort. Eligible participants were WLHIV aged ≥18 years with no history of anal HSIL. Study participants had an examination including collection of cervical/vaginal and anal specimens, followed by high-resolution anoscopy with biopsy. Results: We enrolled 256 women with evaluable anal pathology. The mean age was 49.4 years, 64% women were non-Hispanic black, 67% were former or current smokers, and 56% reported ever having anal sex with a man. The median CD4 T-cell count was 664 cells/μL. The prevalence of anal histologic HSIL (hHSIL) was 27% (95% confidence interval [CI], 22%–33%). There was a strong concordance (240/254) between local and consensus pathologists for hHSIL vs less than hHSIL (κ = 0.86 [95% CI, .79–.93]). Current CD4 count of ≤200 cells/μL was the strongest predictor of consensus anal hHSIL diagnosis (adjusted odds ratio [aOR], 10.34 [95% CI, 3.47–30.87]). History of anoreceptive intercourse was also associated with hHSIL (aOR, 2.44 [95% CI, 1.22–4.76]). Conclusions: The prevalence of anal hHSIL in WLHIV in the United States was 27% in this study where all participants received high-resolution anoscopy and biopsy. Abstract : To determine the true prevalence of anal high-grade squamous intraepithelial lesions in women living with human immunodeficiency virus in the United States, we conducted high-resolution anoscopy and biopsies on all participants in the study. The prevalence was 27%, and substantially higher than previous reports.